2010
DOI: 10.2164/jandrol.109.007880
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal/Permeability‐Increasing Protein Is Associated With the Acrosome Region of Rodent Epididymal Spermatozoa

Abstract: To elucidate the molecular mechanisms involved in sperm maturation during epididymal transit, we intended to isolate secretory molecules that are region-specifically expressed along the epididymis and secreted into the lumen of epididymal ducts. By using differential display screening and DNA sequence analyses, we isolated a rat bactericidal/permeability-increasing protein (BPI) possessing a signal sequence at its N-terminal, which was expressed in the caput region of epididymis, but not in the caudal region. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 46 publications
2
13
0
1
Order By: Relevance
“…It has been suggested that these epididymal granules facilitate the transfer of proteins to the sperm surface during their transit of the organ , Saez, et al, 2003, Yano, et al, 2010. This is in keeping with the demonstration that biotinylated proteins are able to be transferred between epididymosomes and the sperm surface (Saez, et al, 2003).…”
Section: Epididymal Maturationsupporting
confidence: 66%
“…It has been suggested that these epididymal granules facilitate the transfer of proteins to the sperm surface during their transit of the organ , Saez, et al, 2003, Yano, et al, 2010. This is in keeping with the demonstration that biotinylated proteins are able to be transferred between epididymosomes and the sperm surface (Saez, et al, 2003).…”
Section: Epididymal Maturationsupporting
confidence: 66%
“…Cholesterol is particularly abundant in seminal plasma (19) and has an inhibitory effect on sperm capacitation. During capacitation, cholesterol and other sterols are removed from the sperm surface, and non-covalently attached glycoproteins acquired in the epididymis are released from the sperm surface (20). Together, these modifications create a more fluid membrane environment, making the sperm competent for subsequent fertilization cues.…”
Section: Sperm Migration In the Female Reproductive Tractmentioning
confidence: 99%
“…For instance, it has been demonstrated that cystatinrelated epididymal spermatogenic protein has both anti-microbial functions and a role in the sperm-oocyte fusion process. BPI is located in the matrix of the acrosome and attaches to the spermatozoa plasma membrane surface of the acrosomal region (Yano et al 2010). Data from our sperm-oocyte fusion assay suggest that both the N-and C-terminal domains of BPI may be directly involved in the sperm-oocyte fusion process.…”
Section: Discussionmentioning
confidence: 85%
“…Immunofluorescence analysis showed BPI localization in the seminiferous tubule, caput epididymis epithelium, and sperm. Although it has been reported that BPI protein is associated with the acrosome region of mice epididymal spermatozoa (Yano et al 2010), BPI expression was not seen in the epithelia of the corpus and cauda epididymis. Results from sperm-oocyte fusion assays indicated that anti-BPI antiserum may influence the fusion of sperm and oocytes, although the mechanism by which this occurs is still unclear and needs further investigation.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation